2008
DOI: 10.1038/nm1746
|View full text |Cite
|
Sign up to set email alerts
|

Lewy bodies in grafted neurons in subjects with Parkinson's disease suggest host-to-graft disease propagation

Abstract: Two subjects with Parkinson's disease who had long-term survival of transplanted fetal mesencephalic dopaminergic neurons (11-16 years) developed alpha-synuclein-positive Lewy bodies in grafted neurons. Our observation has key implications for understanding Parkinson's pathogenesis by providing the first evidence, to our knowledge, that the disease can propagate from host to graft cells. However, available data suggest that the majority of grafted cells are functionally unimpaired after a decade, and recipient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
1,140
1
26

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 1,612 publications
(1,244 citation statements)
references
References 16 publications
43
1,140
1
26
Order By: Relevance
“…To date, immunohistochemical analysis of transplants surviving longer than 10 years has been reported for 5 cases [20,21,[25][26][27]. Consistent with the imaging data, these transplants that had survived for as many as16 years in the brain contained large numbers of dopaminergic neurons (Fig.…”
Section: Can Neural Grafts Survive and Provide Long-term Function?supporting
confidence: 72%
See 1 more Smart Citation
“…To date, immunohistochemical analysis of transplants surviving longer than 10 years has been reported for 5 cases [20,21,[25][26][27]. Consistent with the imaging data, these transplants that had survived for as many as16 years in the brain contained large numbers of dopaminergic neurons (Fig.…”
Section: Can Neural Grafts Survive and Provide Long-term Function?supporting
confidence: 72%
“…Dopaminergic Grafts Can Survive and Become Morphologically Integrated in the PD Patient's Brain Following implantation of postmitotic DA neuroblasts from the ventral mesencephalon of 6-to 9-weekold human fetuses, positron emission tomography (PET) detected increases in 6-L-[ 18 F]-fluorodopa ( 18 F-dopa) uptake ( Fig. 1) [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], and histopathological studies have shown long-term, extensive synaptic reinnervation in the striatum [13,[20][21][22][23][24][25][26][27].…”
Section: Can Da Neurons Be Replaced and Neural Grafts Have Functionalmentioning
confidence: 99%
“…The patients who came to autopsy after only a few years had clusters of viable dopaminergic neurons that re-innervated areas of the striatum. But after longer incubation periods (12-16 years), α-synuclein and ubiqutin-positive Lewy body pathology was identified in the fetal grafts [25,26]. The presence of metabolically and phenotypically normal dopaminergic grafts early in this process (18 months) suggested a long lag phase before induction of pathology [27][28][29].…”
Section: Spread Of α-Synuclein Pathology To Young Neurons In Human Pamentioning
confidence: 99%
“…Human dopamine cells transplanted and examined postmortem more than a decade after transplant show extensive reinnervation in the putamen [59,61,62,63]. In a small percentage of cells in some centers [61,62], but not others [63], cytoplasmic inclusions resembling Lewy bodies have been observed. Because the overall quality of the dopamine cell transplant and fiber outgrowth remains excellent, the significance of this rare observation is uncertain.…”
Section: Human Dopamine Neurons Survive Indefinitely Without Immunosumentioning
confidence: 99%